Anthropometric indicators for obesity and its relationship with depressive symptoms: analysis of a Peruvian national survey - Vera Ponce, Víctor Juan (2023)
Background: The association between obesity and depression has been frequently reported. However, it still remains unclear which anthropometric indicators for obesity could be the best measure to explain its linkage with depressive symptoms. Methods: This is a cross-sectional analytical study. Secondary data was analyzed using information from the Demographic and Health Survey of Peru (ENDES in Spanish). Data from the years 2018 to 2021 were reviewed. The outcome of interest was the presence of depressive symptoms, assessed with the Patient Health Questionnaire-9 (PHQ-9). The exposure variable was the presence of obesity, which was evaluated by body mass index (BMI) and abdominal circumference. Crude and adjusted odds ratios (cOR and aOR) were calculated using logistic regression. Both prevalence and association measures were presented with 95% confidence intervals (95% CI). Results: A total of 141,134 subjects were included in the study. Depression was present in 2.51% (95% CI 2.38–2.65). Obesity according to BMI was present in 25.42% (95% CI 24.97–25.88), while abdominal obesity was shown in 41.67% (95% CI 41.19–42.15). In the multivariate analysis, a statistically significant association was found in regard to symptoms of depression in patients with abdominal obesity (aOR: 1.13; 95% CI 1.03–1.24), while no association was found with obesity according to BMI. Conclusions: Abdominal circumference could be a better anthropometric measure than BMI to evaluate the association between obesity and depressive symptoms in the Peruvian population.